Characteristics of bio-oil from the pyrolysis of palm kernel shell in a newly developed two-stage pyrolyzer. (15th October 2016) - Oh, Seung-Jin; Choi, Gyung-Goo; Kim, Joo-Sik
Abstract: Pyrolysis of palm kernel shell was performed using a two-stage pyrolyzer consisting of an auger reactor and a fluidized bed reactor within the auger reactor temperature range of ∼290–380 °C at the fluidized bed reactor temperature of ∼520 °C, and with a variable residence time of the feed material in the auger reactor. The highest bio-oil yield of the two-stage pyrolysis was ∼56 wt%. The bio-oil derived from the auger reactor contained degradation products of the hemicelluloses of PKS, such as acetic acid, and furfural, whereas the fluidized bed reactor produced a bio-oil with high concentrations of acetic acid and phenol. The auger reactor temperature and the residence time of PKS in the auger reactor had an influence on the acetic acid concentration in the bio-oil, while their changes did not induce an observable trend on the phenol concentration in the bio-oil derived from the fluidized bed reactor. The maximum concentrations of acetic acid and phenol in bio-oil were ∼78 and 12 wt% dry basis, respectively. As a result, it was possible for the two-stage pyrolyzer to separately produce two different bio-oils in one operation without any costly fractionation process of bio-oils. Highlights: The two-stage pyrolyzer is composed of an auger and a fluidized bed reactor. The two-stage pyrolyzer produced two different bio-oils in a single operation. The maximum bio-oil yield of the two-stage pyrolysis was ∼56 wt%. The maximum concentration of acetic acid in bio-oil was ∼78 wt% dry basis. The maximum concentration of phenol in bio-oil was ∼12 wt% dry basis.